USE OF NON-TRADITIONAL MEANS AND METHODS IN THE DEVELOPMENT AND POPULARIZATION OF BADMINTON SPORT IN UZBEKISTAN - Daniyeva Yarkin Choriyevna; Torayeva daughter of Navbakhor Altiboy (Web of Journals Publishing, 2024)
In recent years, Uzbekistan has witnessed a growing interest in diversifying its sports culture. While football and wrestling have traditionally dominated the athletic landscape, badminton is emerging as a sport with significant potential. Its accessibility, affordability, and appeal to a wide range of age groups make it an ideal candidate for widespread adoption. However, the growth of badminton in Uzbekistan has required innovative strategies, as traditional approaches have often focused on already established sports.
Keywords: Badminton in Uzbekistan, Non-traditional sports development, Grassroots sports programs, Digital campaigns in sports, Inclusive sports initiatives, Badminton training methods, Sports popularization strategies, Public engagement in badminton, Corporate sponsorship in sports.